Penerapan Konsep Gamifikasi Nilai Filosofis Seni Reak dalam Pendidikan Budi Pekerti - Kristining Seva; Willfridus Demetrius Siga (Universitas Pahlawan Tuanku Tambusai, 2022)
This community service prioritizes the documentation method through observation, interviews, and literature studies, which focusing on implementing of gamification in character building education that elevates the philosophical values of Reak's performing arts as its main content. This is closely related to the implementation of the preservation of local wisdom from an early age to the younger generation. A qualitative method with an ethnographic approach through in-depth interviews, focus group discussions by providing training on the Kaulinan Reak board game were uswd to analysed this project. The main targets are children in primary school who live in the vicinity of Reak Tibelat Art Studio, Kampung Jati, Cibiru, Bandung. In addition, strengthening character education is a form of concerning the implementation of habituation, practice, and a good model based on local wisdom. This habituation is realized through a fun learning process using the principles of gamification through board game teaching media and interactive teaching modules. The enthusiasm of the children in learning the philosophical values of Reak was indicated by their keenness in every learning activity using the boardgame.